An interdisciplinary approach in identifying the legitimate regulator of anti-doping in sport: The case of the Australian Football League. Issue 1 (February 2016) - Gowthorp, Lisa; Greenhow, Annette; O'Brien, Danny
Highlights: Actors are perceived to have authority according to level and type of capital they possess. In a social field, dominant actors influence social conditions and behaviors. Perceived authority of actors is not connected with legislative legal authority. The AFL was perceived as a dominant actor in the EFC doping investigation. The AFL had greater levels of symbolic capital than the anti-doping regulator, ASADA. Abstract: The regulation of anti-doping practices in Australian sport is overseen by the Australian Sports Anti-Doping Authority (ASADA), which is a statutory authority funded by the Australian Commonwealth Government (ACG). The 2013 ASADA investigation into the Essendon Football Club (EFC) uncovered the alleged use of performance and image enhancing drugs by a number of players and support personnel. However, despite the call for sanctions to be placed on those taking banned substances, ASADA itself became the central focus of enquiry with the EFC questioning the legitimacy of ASADA's authority in their management of the investigation. Using content analysis and Bourdieu's conceptual framework, this paper aims to determine the legitimate regulatory authority of key actors involved in the EFC investigation. The findings suggest actors in the social field, as related to the case of the EFC investigation, possess varying amounts and types of capital, which cumulatively convert to symbolic capital. Dominant actors within the social field retain more symbolic capital than others and are perceived to possess legitimate regulatory authority, which does not translate to actual legal authority. This apparent disconnect between perceived authority on the one hand and actual legal legitimacy on the other has implications for the future management of such cases, both in the Australian Football League and beyond.